KEDUDUKAN ASAS HUKUM DI INDONESIA : DINAMIKA PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Ari; Khatimul Fitri; Norman (Universitas Islam Negeri Raden Fatah Palembang, 2024)
Legal principles are the fundamental guidelines in the formation of laws and regulations. This study aims to analyze the position of legal principles in the dynamics of law-making in Indonesia, as well as the impact of the application or neglect of legal principles on the quality and legitimacy of the resulting regulations. The research method used is normative legal research with a descriptive approach, which examines legal principles in law-making based on Law No. 12 of 2011 and related regulations. The research findings indicate that legal principles play a central role at every stage of law-making, from drafting to enactment. The application of legal principles such as legal certainty, justice, and transparency can improve the substance of regulations, strengthen legal legitimacy, and enhance public trust in the legal system. Conversely, neglecting legal principles can diminish the quality of regulations, reduce implementation effectiveness, and lead to public dissatisfaction that may result in social conflicts. This study emphasizes the importance of consistent application of legal principles in law-making to create a fair and responsive legal system.